Information Asymmetry, Internal and External Dimensions of Corporate Governance Quality: Improving or Worsening Audit Quality? - Samira Joudi (Shahid Bahonar University of Kerman, 2019)
Objective: This research aims to investigate the effects of asymmetric information on the relationship between audit quality and internal and external dimentions of corporate governance quality, during the period 2008-2017. Method: Multivariate regressions based on panel data model and cross-sectional data were used, regarding Stata and Eviews as the softwares to estimate the models. Discretionary accruals, auditor's tenure and the size of audit firms were considered proxies for audit quality, and the price synchronicity model and the spread model were used to measure information asymmetry. Result: There is a negative relationship between corporate governance and audit quality in the companies with higher information asymmetry. The existence of corporate governance does not improve audit quality, but in the companies with low information asymmetry, there is positive relationship between corporate governance and audit quality. Conclusion: The existence of information asymmetry has greater impacts on audit quality than the corporate governance quality. Also, information asymmetry distorts the positive relationship between corporate governance and audit quality.